Bibliometric Analysis of Value Creation - Loso Judijanto (Westscience Press, 2026)
Value creation has become a central concept in management, innovation, marketing, and sustainability research due to the increasing complexity of business environments and the emergence of new technological and organizational paradigms. This study aims to examine the intellectual structure, research trends, influential contributions, and future directions of value creation research through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to “value creation,” and analyzed using VOSviewer to perform keyword co-occurrence analysis, citation analysis, author co-citation analysis, institutional collaboration analysis, country collaboration analysis, and thematic evolution mapping. The findings reveal that value creation research has developed through several major streams, including business model innovation, innovation capability, sustainability, value co-creation, service-dominant logic, digital transformation, and ecosystem perspectives. The citation analysis identifies business models, customer value, co-creation, and digital transformation as the most influential foundations shaping the field. Furthermore, the temporal analysis demonstrates a shift from traditional value generation perspectives toward emerging themes involving artificial intelligence, circular economy, sustainable business models, and digital ecosystems. The collaboration analysis highlights the dominant contribution of countries such as the United States, China, Germany, and other international research networks in advancing knowledge development. This study contributes by providing a comprehensive visualization of the evolution and current state of value creation research while identifying potential future research opportunities related to the integration of technology, sustainability, and collaborative ecosystems in creating multidimensional value.